Macrophytes of the Baltic Sea ecosystem as a source of raw materials for the food industry - E. V. Ulrikh; N. Yu. Klyuchko; S. V. Agafonova; E. S. Zemlyakova; S. A. Sukhikh; A. V. Kachanova; O. S. Fedorova (Пищевые системы)
Such types of resources as algae, aquatic plants (macrophytes) and their metabolites can be used as sources of biomass for complex processing. The purpose of this study is to study the diversity, peculiarities of growth and production of biologically active substances of macrophytes of the Baltic Sea ecosystem for the food, feed and nutraceutical industries. The macroalgae of the Baltic Sea are promising raw materials for the production of valuable biologically active compounds, as they are easily reproducible, do not require areas and special resources for accumulation. Significant amounts of algae can be found on the shore (storm emissions), that is, obtained without the cost of their extraction. Isolation of a complex of biologically active substances is the most suitable way to use their potential as antibacterial, antioxidant, anticarcinogenic, anti-inflammatory and hepatoprotective agents. Many of the coastal aquatic plants are available and multiply intensively, forming a significant amount of biomass, which currently has insufficient use in various fields of industry, agriculture, forestry, fish farming, medicine, etc. Macrophytes have high nutritional value and are promising raw materials for the isolation of both nutraceuticals and parapharmaceuticals. It is important to study the potential of duckweed for wastewater treatment, while it can be processed into valuable biomass for animal feed and the production of biologically active substances. The coastal aquatic plant radest has antioxidant activity and antibacterial action against both gram-negative and gram-positive microflora. Macrophyte teloresis is widespread in the Kaliningrad region. The high content of macronutrients such as magnesium, calcium and phosphorus in telorez improves the quality of feed and the efficiency of livestock production. In the future, in-depth research is needed into promising areas of processing biomass of aquatic plants in order to obtain biologically active substances for the food, feed and nutraceutical industries.